The Indonesian Government’s Conflict Management in Handling Free Nutritional Meal Program (MBG) Poisoning Crisis - Rasya Raditya Hariana; Bachtiar Dwi Kurniawan (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2026)
The Free Nutritional Meal Program (MBG) was launched by the Indonesian government in 2025 as a national initiative to address stunting, improve child nutrition, and strengthen human resource development. However, its implementation triggered a crisis following food poisoning incidents across multiple provinces, exposing governance, coordination, and communication problems in policy implementation. This study aims to analyze the Indonesian government’s conflict and crisis management in responding to the MBG poisoning crisis, with particular attention to inter-organizational coordination, crisis communication, and policy legitimacy recovery. This research employs a qualitative approach using literature review and document analysis, drawing on Conflict Management Theory, Crisis Management Theory, and Benoit’s Image Restoration Theory. The findings show that the MBG poisoning crisis reflected not only a technical failure in food provision, but also a broader governance crisis characterized by weak early detection, fragmented implementation, and unclear institutional accountability. Cross-ministerial intervention, corrective action, and image restoration strategies became the primary mechanisms for de-escalating conflict, restoring public trust, and preserving policy legitimacy. The study concludes that sustaining the MBG Program requires stronger food safety governance, participatory risk communication, and integrated multi-sectoral coordination to ensure policy effectiveness and long-term public legitimacy.